Role of compliance in Helicobacter pylori eradication treatment: Results of the European Registry on H. pylori management - Huguet, Jose M; Ferrer-Barceló, Luis; Suárez, Patrícia; Barcelo-Cerda, Susana; Sempere, Javier; Saracino, Ilaria Maria; Fiorini, Giulia; Vaira, Dino; Pérez-Aísa, Ángeles; Jonaitis, Laimas; Tepes, Bojan; Castro-Fernandez, M; et al. (United European gastroenterology journal, 2024)
BACKGROUND: Adherence to Helicobacter pylori (H. pylori) eradication treatment is a cornerstone for achieving adequate treatment efficacy. OBJECTIVE: To determine which factors influence compliance with treatment. METHODS: A systematic prospective non-interventional registry (Hp-EuReg) of the clinical practice of European gastroenterologists. Compliance was considered adequate if ≥90% drug intake. Data were collected until September 2021 using the AEG-REDCap e-CRF and were subjected to quality control. Modified intention-to-treat analyses were performed. Multivariate analysis carried out the factors associated with the effectiveness of treatment and compliance. RESULTS: Compliance was inadequate in 646 (1.7%) of 38,698 patients. The non-compliance rate was higher in patients prescribed longer regimens (10-, 14-days) and rescue treatments, patients with uninvestigated dyspepsia/functional dyspepsia, and patients reporting adverse effects. Prevalence of non-adherence was lower for first-line treatment than for rescue treatment (1.5% vs. 2.2%; p < 0.001). Differences in non-adherence in the three most frequent first-line treatments were shown: 1.1% with proton pump inhibitor + clarithromycin + amoxicillin; 2.3% with proton pump inhibitor clarithromycin amoxicillin metronidazole; and 1.8% with bismuth quadruple therapy. These treatments were significantly more effective in compliant than in non-compliant patients: 86% versus 44%, 90% versus 71%, and 93% versus 64%, respectively (p < 0.001). In the multivariate analysis, the variable most significantly associated with higher effectiveness was adequate compliance (odds ratio, 6.3 [95%CI, 5.2-7.7]; p < 0.001). CONCLUSIONS: Compliance with Helicobacter pylori eradication treatment is very good. Factors associated with poor compliance include uninvestigated/functional dyspepsia, rescue-treatment, prolonged treatment regimens, the presence of adverse events, and the use of non-bismuth sequential and concomitant treatment. Adequate treatment compliance was the variable most closely associated with successful eradication.
Keywords: Registries; klarithromycin; hodnocení adherence k farmakoterapii; rescue; Humans; Metronidazole; adverse effects; bismuth; lidé středního věku; registrace; Evropa; effectiveness; Female; Aged; dospělí; adherence; Bismuth; výsledek terapie; Clarithromycin; senioři; lidé; Dyspepsia; antibakteriální látky; dyspepsie; bismut; Europe; Assessment of Medication Adherence; rate; amoxicilin; Proton Pump Inhibitors; dyspepsia; Adult; ženské pohlaví; Helicobacter Infections; Anti-Bacterial Agents; Helicobacter pylori; Male; Middle Aged; inhibitory protonové pumpy; Treatment Outcome; first line; efficacy; Amoxicillin; mužské pohlaví; prospektivní studie; metronidazol; kombinovaná farmakoterapie; regimens; infekce vyvolané Helicobacter pylori; Drug Therapy, Combination; Prospective Studies